Influences of carbon sources and plant growth regulators on in vitro rooting of Lycium chinense - Kim, June Bong; Kim, Nam Su; Lim, Jinsu; Kim, Kihyun; Lee, Minhwan; Uddin, Md Romij; Sathasivam, Ramaraj; Park, Chanung; Park, Sang Un (Journal of Phytology, 2025)
In vitro propagation of Lycium chinense is very important, which contributes to its effective multiplication as well as preservation. Accordingly, this study aimed to explore the influence of different carbon sources, auxins, silver nitrate (AgNO3), and putrescine on in vitro shoot regeneration and rooting from stem explants of L. chinense. Young shoots were generated on hormone-free Murashige and Skoog (MS) basal medium, and root and shoot experiments were then conducted to evaluate their effects. Among different carbon sources, sucrose (at 130 mM) and glucose significantly promoted root regeneration (highest number and length of roots). Of the auxins, the best root production occurred with indol-3-butyric acid (IBA) at 0.5 mg/L, and IAA and NAA generated root production at less than optimal levels with increased concentration. The co-application of IBA (0.5 mg/L) with AgNO3 or putrescine enhanced shoot regeneration. The best rate of shoot production was observed with putrescine on both concentrations of AgNO3 (5 mg/L on AgNO3 and 100 mg/L on putrescine respectively) indicating the capability of these substances to enhance in vitro culture systems. These results will contribute to improving the efficiency of L. chinense regeneration via adventitious shoots through an easy setup of the culture conditions with an interest in propagation and other biotechnological applications.